What happens after the passage of reform initiatives? Two dimensions of social policy reform in Korea. (March 2014) - Lee, Jooha
This article aims to present a comprehensive analysis of social policy reform, encompassing its two dimensions, that is, reform decision-making and implementation, with reference to Korea's new social assistance programme. In the social policy reform after the economic crisis of 1997, less was delivered locally than decided centrally. First, there were decision deficits centrally, which became visible locally. This was considerably attributable to the fact that the decision-making process after 'framework legislation' was passed showed more active involvement of conservative forces 'from above' – despite the new-found importance of pro-welfare forces 'from below'. Second, there were implementation deficits locally. This article explains the reasons why legislated policy was not implemented as designed in the light of three barriers to implementation. Although a powerful government may be able to steer reform through central decision making, it is not necessarily in control of effective implementation at the local level. Points for practitioners: Today's decision making in a lately democratized country such as Korea reflects the increase of power resources available to societal groups, but state officials play a more pivotal role, especially during the enforcement preparation process (the second round of decision making). Attention needs to be paid to the interplays between them, which may be particular to time and place. Changes in policy goals and contents at the central decision-making level do not always result in intended changes in implementation. The analysis of decision making should thus be followed by an investigation of implementation, which is rarely performed in the international literature on welfare reform.